Method for preparing 4A zeolite from high-iron red mud

By roasting high-speed iron red mud and sodium carbonate under a reducing atmosphere, preparing sodium aluminate and combining hydrothermal crystallization method, the problems of high production cost of 4A zeolite and low resource utilization rate of red mud are solved, and cost reduction and environmental pollution are achieved ease.

CN119118148APending Publication Date: 2024-12-13BINZHOU YINGKUNYUAN WOOD FIRE NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411287847.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The production cost of 4A zeolite is high and the utilization rate of red mud resources is low, resulting in high production costs and environmental pollution problems.

Method used

Mix high-iron red mud with sodium carbonate in a reducing atmosphere for reduction and roasting to obtain sodium aluminate and magnetic iron materials. The 4A zeolite is prepared by leaching, evaporation and concentration, irrigation and hydrothermal crystallization, and reduce production Cost and increase the utilization rate of red mud.

Benefits of technology

It effectively reduces the production cost of 4A zeolites, improves the utilization rate of red mud, solves the environmental problems caused by red mud storage, and realizes the resource utilization of red mud.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118148A_ABST
    Figure CN119118148A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing 4A zeolite from high-iron red mud, and relates to the technical field of comprehensive utilization of the high-iron red mud. The high-iron red mud and sodium carbonate are subjected to reduction roasting and leaching to obtain a sodium aluminate solution, and zeolite mother liquor is evaporated and then used for preparing a sodium silicate solution through a wet method; and carrying out slurrying and hydrothermal crystallization on the sodium aluminate solution and the sodium silicate solution to prepare a 4A zeolite product. The high-iron red mud has the characteristics of high aluminum and low silicon, a sodium aluminate solution with relatively high quality can be obtained by adding a certain amount of sodium carbonate in the reduction roasting process, the method is very suitable for production of the 4A zeolite, and the production cost of the 4A zeolite is greatly reduced by applying the sodium aluminate extracted by reduction roasting of the red mud to production of the 4A zeolite. Meanwhile, sodium silicate is prepared from concentrated 4A zeolite mother liquor and quartz sand, and the cost is low. According to the method, the production cost of the 4A zeolite can be reduced, and resource utilization of the red mud can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of comprehensive utilization of high-iron red mud, and in particular to a method for preparing 4A zeolite by utilizing high-iron red mud. Background Art

[0002] As a molecular sieve product with excellent performance, 4A zeolite is currently widely used in detergent additives, adsorption, plastic stabilizers and other industries.

[0003] Since the 1990s, 4A zeolite production companies have been established and developed continuously. There are many methods for producing 4A zeolite, among which the hydrothermal synthesis method is more common. The raw materials of the hydrothermal synthesis method are sodium silicate and sodium aluminate, and the preparation methods of sodium aluminate are different: some use aluminum hydroxide as a raw material and dissolve sodium hydroxide to prepare sodium aluminate; some use sodium aluminate solution in the production process of sintered alumina to directly prepare 4A zeolite. In recent years, many companies directly use the aluminum hydroxide decomposition mother liquor produced by the Bayer process of alumina to directly react with sodium silicate to prepare 4A zeolite.

[0004] In summary, the raw materials for the current production of 4A zeolite are basically soda ash water glass, aluminum hydroxide and sodium hydroxide solution. The price of raw materials is relatively high, resulting in the high production cost of 4A zeolite. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing 4A zeolite by using high-iron red mud. The present invention can not only reduce the production cost of 4A zeolite, but also realize the resource utilization of red mud.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing 4A zeolite by using high-iron red mud, comprising the following steps:

[0008] The high iron red mud is mixed with sodium carbonate, and reduction roasted in a reducing atmosphere to obtain a roasted material; the roasted material comprises sodium aluminate and a magnetic iron material; the mass content of Fe in the high iron red mud is greater than 45%, the mass content of SiO2 is less than 3%, and the mass content of Al2O3 is greater than 12%;

[0009] Leaching the roasted material with 4A zeolite washing liquid, separating the solid and the liquid, and obtaining a sodium aluminate solution;

[0010] The 4A zeolite mother liquor is evaporated and concentrated to obtain a caustic soda solution;

[0011] The caustic soda solution is mixed with quartz sand for leaching to obtain a sodium silicate solution;

[0012] The sodium aluminate solution and the sodium silicate solution are mixed, and slurrying and hydrothermal crystallization are performed in sequence to obtain 4A zeolite.

[0013] Preferably, the molar amount of the sodium carbonate is calculated as Na2O, and the molar ratio of Al2O3 to Na2O in the high-iron red mud is 1:(1.05-1.3).

[0014] Preferably, the reduction roasting is carried out at a temperature of 850 to 1200° C. and for a time of 1 to 2 hours.

[0015] Preferably, the concentration of Na2O in the 4A zeolite washing solution is ≤20 g / L, calculated as Na2O;

[0016] The liquid-to-solid ratio of the 4A zeolite washing liquid to the roasting material is (1.5-5) L:1 kg.

[0017] Preferably, the leaching temperature is 60-95° C. and the leaching time is 0.5-1 h.

[0018] Preferably, calculated as Na2O, the Na2O in the caustic soda solution is greater than 240 g / L.

[0019] Preferably, the boiling temperature is 90-180° C. and the time is 2-4 hours.

[0020] Preferably, the modulus of the sodium silicate solution is 2.1 to 2.5, and the SiO2 mass content is greater than 260 g / L.

[0021] Preferably, the molar amount of the sodium aluminate solution is calculated as Al2O3, and the molar amount of the sodium silicate solution is calculated as SiO2, and the molar ratio of SiO2 to Al2O3 during slurrying is (2 to 2.1):1.

[0022] Preferably, the hydrothermal crystallization temperature is 75-85° C. and the time is 2-3 hours.

[0023] The invention provides a method for preparing 4A zeolite by utilizing high-iron red mud. The method comprises the following steps: mixing high-iron red mud with sodium carbonate, and performing reduction roasting in a reducing atmosphere to obtain a roasting material; the roasting material comprises sodium aluminate and a magnetic iron material; the mass content of Fe in the high-iron red mud is greater than 45%, the mass content of SiO2 is less than 3%, and the mass content of Al2O3 is greater than 12%; leaching the roasting material with a 4A zeolite washing liquid, performing solid-liquid separation, and obtaining a sodium aluminate solution; evaporating and concentrating the 4A zeolite mother liquor to obtain a caustic soda solution; mixing the caustic soda solution with quartz sand for leaching to obtain a sodium silicate solution; mixing the sodium aluminate solution and the sodium silicate solution, performing slurrying and hydrothermal crystallization in sequence, and obtaining the 4A zeolite. High-iron red mud has the characteristics of high aluminum and low silicon. During the reduction roasting process, a certain amount of sodium carbonate is added to obtain a high-quality sodium aluminate solution, which is very suitable for the production of 4A zeolite. The sodium aluminate extracted by red mud reduction roasting is applied to the production of 4A zeolite, which greatly reduces the production cost of 4A zeolite. At the same time, the present invention prepares sodium silicate by concentrating the 4A zeolite mother liquor and mixing it with quartz sand, and the cost is also low.

[0024] In addition, it is well known that red mud is the waste residue produced after alumina is extracted from bauxite. The amount of red mud produced is very large. Generally, 0.6 to 1.2 tons of red mud will be produced for every ton of alumina produced, but the utilization rate is extremely low. It is estimated that the global stockpile of red mud has exceeded 3 billion tons, and the amount of red mud produced in China alone exceeds 100 million tons per year, most of which are disposed of by stockpiling. Due to the large amount of red mud produced and the large amount of accumulated stockpiling, a large area of ​​land is occupied. The present invention uses red mud as raw material to prepare 4A zeolite, which not only reduces the production cost of 4A zeolite, but also improves the utilization rate of red mud, realizes the resource utilization of red mud, and is conducive to alleviating the environmental problems caused by red mud stockpiling. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Flow chart for preparing 4A zeolite product for each example. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing 4A zeolite by using high-iron red mud, comprising the following steps:

[0027] The high iron red mud is mixed with sodium carbonate, and reduction roasted in a reducing atmosphere to obtain a roasted material; the roasted material comprises sodium aluminate and a magnetic iron material; the mass content of Fe in the high iron red mud is greater than 45%, the mass content of SiO2 is less than 3%, and the mass content of Al2O3 is greater than 12%;

[0028] Leaching the roasted material with 4A zeolite washing liquid, separating the solid and the liquid, and obtaining a sodium aluminate solution;

[0029] The 4A zeolite mother liquor is evaporated and concentrated to obtain a caustic soda solution;

[0030] The caustic soda solution is mixed with quartz sand for leaching to obtain a sodium silicate solution;

[0031] The sodium aluminate solution and the sodium silicate solution are mixed and sequentially slurried and hydrothermally crystallized to obtain 4A zeolite.

[0032] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0033] The invention mixes high-iron red mud with sodium carbonate, and performs reduction roasting in a reducing atmosphere to obtain a roasted material; the roasted material comprises sodium aluminate and a magnetic iron material.

[0034] In the present invention, the mass content of Fe in the high-iron red mud is preferably greater than 45%, the mass content of SiO2 is preferably less than 3%, and the mass content of Al2O3 is preferably greater than 12%.

[0035] In the present invention, the molar amount of the sodium carbonate is calculated as Na2O, and the molar ratio of Al2O3 to Na2O in the high iron red mud is preferably 1:(1.05-1.3). In the embodiments of the present invention, it can be specifically 1:1.05, 1:1.1, 1:1.15 or 1:1.2.

[0036] The present invention has no special requirements for the reducing atmosphere, and any reducing atmosphere known in the art can be used, such as a hydrogen atmosphere or an atmosphere containing CO. In an embodiment of the present invention, the reducing gas used in the reducing atmosphere is a mixed gas produced by carbon-containing materials in a low-oxygen environment, wherein the volume content of CO is 60%.

[0037] In the present invention, the reduction roasting temperature is preferably 850-1200°C, and in the embodiment of the present invention, it can be 860, 890, 980, 1020, 1100, 1150 or 1200°C; the reduction roasting time is preferably 1-2h, and in the embodiment of the present invention, it can be 1, 1.5 or 2h. In the present invention, the reduction roasting is preferably carried out in a rotary kiln.

[0038] In the reduction roasting process of the present invention, sodium carbonate is decomposed into Na2O, Al2O3 in the high-iron red mud reacts with Na2O to generate sodium aluminate, and most of the ferric oxide is reduced to elemental iron or ferroferric oxide, both of which are magnetic, to finally obtain a roasting material including sodium aluminate and magnetic iron material (elemental iron and / or ferroferric oxide).

[0039] After the roasting material is obtained, the present invention uses 4A zeolite washing liquid to leach the roasting material, separate the solid and the liquid, and obtain a sodium aluminate solution.

[0040] In the present invention, the concentration of Na2O in the 4A zeolite washing solution is preferably ≤20 g / L in terms of Na2O; in the embodiments of the present invention, the concentration of Na2O in the 4A zeolite washing solution can be specifically 16.87, 16.33 or 20 g / L. In the present invention, the liquid-solid ratio of the 4A zeolite washing solution to the roasting material is preferably (1.5-5) L:1 kg, abbreviated as 1.5-5; in the embodiments of the present invention, it can be specifically 1.88, 2.11, 3.11 or 1.58.

[0041] In the present invention, the leaching temperature is preferably 60-95°C. In the embodiment of the present invention, the leaching temperature can be 86, 82 or 92°C. The leaching time is preferably 0.5-1h, and can be 0.5 or 1h. The present invention dissolves sodium aluminate into 4A zeolite washing liquid by leaching. The present invention uses 4A zeolite washing liquid as the leaching liquid, which has the advantages of being economical and environmentally friendly.

[0042] The present invention has no special requirements for the solid-liquid separation method, and any solid-liquid separation method known in the art can be used.

[0043] The present invention evaporates and concentrates 4A zeolite mother liquor to obtain caustic soda solution.

[0044] The present invention has no special requirements for the evaporation and concentration conditions, and the evaporation and concentration conditions known in the art can be used. In terms of Na2O, the present invention preferably evaporates and concentrates until the Na2O in the caustic soda solution is greater than 240 g / L; in the embodiments of the present invention, the concentration of Na2O in the caustic soda solution is specifically 256, 262, 240.33 or 271 g / L.

[0045] After obtaining the caustic soda solution, the present invention mixes the caustic soda solution with quartz sand for leaching to obtain a sodium silicate solution.

[0046] In the present invention, the quartz sand is preferably high-purity quartz sand (SiO2 mass content>99%). In the present invention, the leaching temperature is preferably 90-180°C, and the time is preferably 2-4 hours. In an embodiment of the present invention, the leaching temperature can be specifically 172, 168, 166 or 176°C; the leaching time can be specifically 2, 3 or 4 hours.

[0047] The present invention has no special requirements for the amount of the caustic soda solution and quartz sand, as long as the modulus of the final sodium silicate solution is 2.1-2.5 and the SiO2 mass content is greater than 260 g / L. In an embodiment of the present invention, the modulus of the sodium silicate solution is specifically 2.31, 2.29, 2.14 or 2.36, and the SiO2 mass content is specifically 269.24, 277.51, 278.36 or 280.56 g / L.

[0048] After the digestion is completed, the present invention preferably allows the obtained slurry to settle, and then separates the solid and liquid to obtain a sodium silicate solution.

[0049] After obtaining the sodium aluminate solution and the sodium silicate solution, the present invention mixes the sodium aluminate solution and the sodium silicate solution and sequentially performs slurrying and hydrothermal crystallization to obtain 4A zeolite.

[0050] In the present invention, the molar amount of the sodium aluminate solution is calculated as Al2O3, and the molar amount of the sodium silicate solution is calculated as SiO2. During slurrying, the molar ratio of SiO2 to Al2O3 is preferably (2 to 2.1):1. In the embodiments of the present invention, it can be specifically 2.06:1, 2.03:1, 2.1:1 or 2.01:1.

[0051] The present invention has no special requirements for the slurrying process, and a slurrying process well known in the art can be used to form a uniform gel-like substance.

[0052] In the present invention, the hydrothermal crystallization temperature is preferably 75-85°C, and the time is preferably 2-3 hours. In an embodiment of the present invention, the hydrothermal crystallization temperature can be specifically 76, 77, 80 or 81°C; and the hydrothermal crystallization time is specifically 3 hours.

[0053] After the hydrothermal crystallization is completed, the present invention preferably separates the obtained slurry, washes the solid and dries it to obtain qualified 4A zeolite.

[0054] The method for preparing 4A zeolite using high-iron red mud provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0055] Figure 1 Flow chart for preparing 4A zeolite product for each example.

[0056] Example 1

[0057] The high iron red mud has a TFe content of 46.83%, an Al2O3 content of 13.61%, and a SiO2 content of 2.45%. Sodium carbonate is added according to a molar ratio of Al2O3 to Na2O of 1:1.05, and the mixture is evenly mixed. The mixture is put into a rotary kiln and calcined at 860°C for 1 hour under reducing conditions. The calcined material is leached with 4A zeolite washing liquid with a Na2O concentration of 16.87 g / L at a liquid-to-solid ratio of 1.88, a leaching temperature of 86°C, and a leaching time of 0.5 h. The solid is a high iron full magnetic powder with a TFe content of 59.69%, a sodium aluminate solution with a Na2O concentration of 65.13 g / L, and an Al2O3 concentration of 56.32 g / L.

[0058] Use 4A zeolite evaporation mother liquor with a Na2O concentration of 256g / L and high-quality quartz sand (SiO2 content > 99%), cook at a high temperature of 172°C for 4 hours, and after the slurry is settled and separated, the modulus of the obtained sodium silicate solution is 2.31 and the SiO2 content is 269.24g / L.

[0059] According to the SiO2 / Al2O3 molar ratio of 2.06:1, sodium aluminate and sodium silicate solutions were slurried at low temperature and crystallized at 80°C for 3 hours. After the slurry was separated, washed and dried, a qualified 4A zeolite product was obtained.

[0060] Example 2

[0061] The high-iron red mud has a TFe content of 47.52%, an Al2O3 content of 13.89%, and a SiO2 content of 2.88%. Sodium carbonate is added according to a molar ratio of Al2O3 to Na2O of 1:1.1, and the mixture is mixed. The mixture is then put into a rotary kiln and roasted at 890°C for 1 hour under reducing conditions. The roasted material is leached with 4A zeolite washing liquid with a Na2O concentration of 16.33 g / L at a liquid-to-solid ratio of 2.11, a leaching temperature of 82°C, and a leaching time of 0.5 h. The solid is a high-iron full magnetic powder with a TFe content of 60.33%, a sodium aluminate solution with a Na2O concentration of 64.22 g / L, and an Al2O3 concentration of 52.14 g / L.

[0062] The 4A zeolite evaporation mother liquor with a Na2O concentration of 262g / L and high-quality quartz sand were boiled at a high temperature of 168°C for 4 hours. After the slurry was settled and separated, the modulus of the obtained sodium silicate solution was 2.29 and the SiO2 content was 277.51g / L.

[0063] Sodium aluminate and sodium silicate solutions were slurried according to a SiO2 / Al2O3 molar ratio of 2.03:1 and crystallized at 81°C for 3 hours. After the slurry was separated, washed and dried, a qualified 4A zeolite product was obtained.

[0064] Example 3

[0065] The high-iron red mud has a TFe content of 48.91%, an Al2O3 content of 12.61%, and a SiO2 content of 2.21%. Sodium carbonate is added according to a molar ratio of Al2O3 to Na2O of 1:1.15, and the mixture is evenly mixed. The mixture is then put into a rotary kiln and roasted at 1020°C for 1 hour under reducing conditions. The roasted material is leached with 4A zeolite washing liquid with a Na2O concentration of 20 g / L at a liquid-to-solid ratio of 3.11, a leaching temperature of 92°C, and a leaching time of 0.5 h. The solid is high-iron full magnetic powder with a TFe content of 61.86%, a sodium aluminate solution with a Na2O concentration of 66.36 g / L, and an Al2O3 concentration of 49.45 g / L.

[0066] The 4A zeolite evaporation mother liquor with a Na2O concentration of 240.33 g / L and high-quality quartz sand were boiled at a high temperature of 166°C for 4 hours. After the slurry was settled and separated, the modulus of the obtained sodium silicate solution was 2.14 and the SiO2 content was 278.36 g / L.

[0067] Sodium aluminate and sodium silicate solutions were slurried according to a SiO2 / Al2O3 molar ratio of 2.1:1 and crystallized at 76°C for 3 hours. After the slurry was separated, washed and dried, a qualified 4A zeolite product was obtained.

[0068] Example 4

[0069] The high iron red mud has a TFe content of 50.11%, an Al2O3 content of 12.09%, and a SiO2 content of 2.03%. Sodium carbonate is added according to a molar ratio of Al2O3 to Na2O of 1:1.2, and the mixture is evenly mixed. The mixture is then put into a rotary kiln and roasted at 980°C for 1 hour under reducing conditions. The roasted material is leached with 4A zeolite washing liquid with a Na2O concentration of 16.33 g / L at a liquid-to-solid ratio of 1.58, a leaching temperature of 86°C, and a leaching time of 0.5 h. The liquid-solid separation is performed, and the solid is a high iron full magnetic powder with a TFe content of 63.46%, a sodium aluminate solution with a Na2O concentration of 60.25 g / L, and an Al2O3 concentration of 51.01 g / L.

[0070] The 4A zeolite evaporation mother liquor with a Na2O concentration of 271g / L and high-quality quartz sand were boiled at a high temperature of 176°C for 4 hours. After the slurry was settled and separated, the modulus of the obtained sodium silicate solution was 2.36 and the SiO2 content was 280.56g / L.

[0071] Sodium aluminate and sodium silicate solutions were slurried according to a SiO2 / Al2O3 molar ratio of 2.01:1 and crystallized at 77°C for 3 hours. After the slurry was separated, washed and dried, a qualified 4A zeolite product was obtained.

[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing 4A zeolite using high-iron red mud, characterized in that: The following steps are involved: The high iron red mud is mixed with sodium carbonate, and reduction roasted in a reducing atmosphere to obtain a roasted material; the roasted material comprises sodium aluminate and a magnetic iron material; the mass content of Fe in the high iron red mud is greater than 45%, the mass content of SiO2 is less than 3%, and the mass content of Al2O3 is greater than 12%; Leaching the roasted material with 4A zeolite washing liquid, separating the solid and the liquid, and obtaining a sodium aluminate solution; The 4A zeolite mother liquor is evaporated and concentrated to obtain a caustic soda solution; The caustic soda solution is mixed with quartz sand for leaching to obtain a sodium silicate solution; The sodium aluminate solution and the sodium silicate solution are mixed, and slurrying and hydrothermal crystallization are performed in sequence to obtain 4A zeolite.

2. The method according to claim 1, characterized in that The molar amount of the sodium carbonate is calculated as Na2O, and the molar ratio of Al2O3 to Na2O in the high-iron red mud is 1:(1.05-1.3).

3. The method according to claim 1 or 2, characterized in that: The reduction roasting temperature is 850-1200° C. and the time is 1-2 hours.

4. The method according to claim 1, characterized in that: Calculated as Na2O, the concentration of Na2O in the 4A zeolite washing solution is ≤20 g / L; The liquid-to-solid ratio of the 4A zeolite washing liquid to the roasting material is (1.5-5) L:1 kg.

5. The method according to claim 1 or 4, characterized in that: The leaching temperature is 60-95° C. and the leaching time is 0.5-1 h.

6. The method according to claim 1, characterized in that Calculated in terms of Na2O, the Na2O in the caustic soda solution is greater than 240 g / L.

7. The method according to claim 1, characterized in that The soaking temperature is 90-180° C. and the time is 2-4 hours.

8. The method according to claim 1, 6 or 7, characterized in that: The modulus of the sodium silicate solution is 2.1-2.5, and the mass content of SiO2 is greater than 260 g / L.

9. The method according to claim 1, characterized in that: The molar amount of the sodium aluminate solution is calculated as Al2O3, and the molar amount of the sodium silicate solution is calculated as SiO2. During slurrying, the molar ratio of SiO2 to Al2O3 is (2-2.1):

1.

10. The method according to claim 1 or 9, characterized in that: The temperature of the hydrothermal crystallization is 75-85° C. and the time is 2-3 hours.

Citation Information

Patent Citations

  • Method for producing 4A zeolite by using waste aluminum oxide and quartz sand

    CN103787361A

  • Method for preparing 4A zeolite from red mud solution and bauxite chemical desilication solution

    CN110451523A

  • Method for separating and recovering aluminum and iron from high-iron red mud

    CN112410559A